Mechanistic Investigation into Crystallization of Hydrated Co-Amorphous Systems of Flurbiprofen and Lidocaine - Xiaoyue Xu; Holger Grohganz; Justyna Knapik-Kowalczuk; Marian Paluch; Thomas Rades (Pharmaceutics)
Background: It is generally accepted that water as a plasticizer can decrease the glass transition temperatures (Tgs) of amorphous drugs and drug delivery systems, resulting in physical instabilities. However, a recent study has reported an anti-plasticizing effect of water on amorphous lidocaine (LID). In co-amorphous systems, LID might be used as a co-former to impair the plasticizing effect of water. Method: Flurbiprofen (FLB) was used to form a co-amorphous system with a mole fraction of LID of 0.8. The effect of water on the stability of co-amorphous FLB-LID upon hydration was investigated. The crystallization behaviors of anhydrous and hydrated co-amorphous FLB-LID systems were measured by an isothermal modulated differential scanning calorimetric (iMDSC) method. The relaxation times of the co-amorphous FLB-LID system upon hydration were measured by a broadband dielectric spectroscopy (BDS), and the differences in Gibbs free energy (ΔG) and entropy (ΔS) between the amorphous and crystalline phases were determined by differential scanning calorimetry (DSC). Results: It was found that the crystallization tendency of co-amorphous FLB-LID decreased with the addition of water. Molecular mobility and thermodynamic factors were both investigated to explain the difference in crystallization tendencies of co-amorphous FLB-LID upon hydration. Conclusions: The results of the study showed that LID could be used as an effective co-former to decrease the crystallization tendency of co-amorphous FLB-LID upon hydration by enhancing the entropic (ΔS) and thermodynamic activation barriers (TΔS)3/ΔG2) to crystallization.